Bicha não morre, vira purpurina : análise do documentário Dzi Croquettes - Magalhães, Michael Roan Domingues (2024)
This work focuses on the documentary "Dzi Croquettes" (2009), directed by Tatiana Issa, as the subject of study, aiming to analyze its narrative and form, highlighting the role of the narrator. The term "documentary" is redefined following the perspectives of Fernão Ramos and Noël Carroll, in order to distance the text from traditional notions of truth and objectivity, emphasizing the author's intent and the social indexing of the genre. An overview of gender identity theories discussed by Judith Butler and Paul B. Preciado is presented, with Foucault serving as a common thread among these theorists, exploring the intersection of sexuality, discourse, knowledge, and power. Additionally, the study incorporates performance studies using Diana Taylor's theories to employ an immanent analysis based on Ismail Xavier, with the intention of examining the expression of transient and non-binary gender within the group. Through this close examination of the documentary, this study aims to contribute to the discourse on Drag identity and its boundaries, particularly in light of the author's personal experiences as a drag queen, emphasizing the historical and political significance of the Dzi Croquettes group in a context of resistance against the "gender ideology" and highlighting the existence of the body beyond normative binary categories.